2016
DOI: 10.1227/neu.0000000000001088
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Regional Brain Hypothermia Inhibits Acute Aquaporin-4 Surge and Sequential Microvascular Events in Ischemia/Reperfusion Injury

Abstract: AQP4, aquaporin-4BBB, blood-brain barrierIba1, ionized calcium-binding adapter molecule 1ICA, internal carotid arteryICAM-1, intracellular adhesion molecule-1I/R, ischemia/reperfusionMCAO, middle cerebral artery occlusionMMP-9, matrix metalloproteinase-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 26 publications
5
46
0
Order By: Relevance
“…The present study demonstrated that transarterial regional hypothermia exerts robust neuroprotective effects in the pMCAO with tCHP model, as well as the typical tMCAO model, as reported previously (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009). This therapy significantly improved neurological deficits and decreased infarct/edema volumes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present study demonstrated that transarterial regional hypothermia exerts robust neuroprotective effects in the pMCAO with tCHP model, as well as the typical tMCAO model, as reported previously (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009). This therapy significantly improved neurological deficits and decreased infarct/edema volumes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015). However, the effects of this therapy have only been examined in a typical ischemic stroke model, the transient middle cerebral artery occlusion (tMCAO) model (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009), which is a complete reperfusion model (Fluri et al, 2015;Takahashi et al, 2012;Zhao and Steinberg, 2011). The effects of this therapy have not yet been investigated in other ischemic stroke models, even though ischemic stroke in humans is extremely diverse in its pattern of occlusion and reperfusion in actual clinical settings.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations